Pengolahan Buah Pisang Menjadi Pinangun (Pisang Nugget Donowangun) Sebagai Upaya Peningkatan Pendapatan Masyarakat Desa Donowangun - Natal Kristiono; Indri Astuti; Fitri Hidayati (IAI Darussalam, 2020)
Donowangun Village, Talun District, has excellent plantation potential, one of the abundant commodities is banana. Banana fruit is a food material that has high economic value. The availability of bananas during the harvest season causes the price of bananas to decline. Of course, action needs to be taken so that prices do not fall too sharply. This problem condition is the basis of the Banana Fruit Processing Training activity to Pinangun (Banana Nugget Donowangun) in Donowangun Village. The purpose of this activity is to process bananas into processed products with high economic value, namely by making banana nuggets. The abundant availability of bananas certainly does not make it difficult for the surrounding community to later open a banana nugget business which has high economic value so that they have high hopes for increasing the market share of this banana fruit. In this activity the UNNES KKN team provided material on the future prospects of the nugget banana processing business. The next material is training on processing banana nuggets that are ready to be produced and have high selling value and proper packaging. The methods used are creative lectures, practice / demonstrations and discussions. The result of this activity is the increased insight and knowledge of PKK Donowangun Village women regarding banana processing. It is hoped that later it will motivate PKK women to create a home industry for banana nuggets.